Optimizing the Role of Non-formal and Informal Education in Realizing Independent and Sustainable Village Innovations - Zulkarnain Zulkarnain; Kukuh Miroso Raharjo; M. Khoirul Fatihin; Decky Avriliand (Universitas Negeri Padang, 2022)
Strengthening the potential of rural communities, one of which is the government's efforts in developing villages through community empowerment which is packaged in the Village Innovation program, namely an empowerment program to improve the welfare of rural communities through optimizing the use of village funds. The purposes of this paper are: (1) to describe the Independent Village Innovation Program and Inclusive Village, (2) to describe the role of non-formal education in realizing village innovation, (3) a case of community empowerment through social capital-based tourism village management in realizing independent innovation villages. The conclusions are as follows: (1) Realizing independent and dignified village innovations needs to be implemented by institutionalizing innovation with the principles of accountability, transparency, and participation, (2) Profiles of graduates from out-of-school education study programs have competencies that are in accordance with the tasks and competencies required by village assistants by ministry of villages, (3) Synergy between the Ministry of Villages, Development of Disadvantaged Regions and Transmigration with universities, one of which is non-formal education study programs should be a must in carrying out state responsibilities for the welfare of its people as a whole.Keywords: Non-formal, informal education, village innovation